2013
DOI: 10.1111/hepr.12098
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan for improvement of hepatic edema: A phase 3, multicenter, randomized, double‐blind, placebo‐controlled trial

Abstract: Add-on therapy with tolvaptan was effective for the treatment of hepatic edema and ascites-related clinical symptoms. Furthermore, tolvaptan is expected to improve low serum sodium concentration and to exert its effect regardless of serum albumin level. Add-on therapy with tolvaptan is therefore considered to be a novel therapeutic option for hepatic edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
176
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(187 citation statements)
references
References 22 publications
7
176
0
2
Order By: Relevance
“…Hypoalbuminemia was common in these patients (average serum albumin levels were around 2.8 g/dL) [11,12].…”
Section: Introductionmentioning
confidence: 92%
“…Hypoalbuminemia was common in these patients (average serum albumin levels were around 2.8 g/dL) [11,12].…”
Section: Introductionmentioning
confidence: 92%
“…This therapeutic mechanism has the potential to improve cirrhosisinduced ascites, and may decrease the need for paracentesis, cell-free and concentrated ascites reinfusion therapy, and transjugular intrahepatic portosystemic shunt placement. A phase III trial of tolvaptan in Japan observed a marked reduction in fluid retention in patients with refractory ascites due to cirrhosis (4 …”
Section: Introductionmentioning
confidence: 99%
“…There was a significant reduction in weight in the tolvaptan group, compared with placebo (-1.95 kg vs -0.44 kg; P < 0.0001), and this benefit held true, even in patients with serum albumin <2.5 g/dL. (28) . In summary there is conclusive evidence that serum hyponatremia has strong correlation to the severeity of complication of liver cirrhosis.…”
Section: Hrs Typementioning
confidence: 83%